Controlling the substrate selectivity of deacetoxycephalosporin/deacetylcephalosporin C synthase. - Lloyd, MD; Lipscomb, S; Hewitson, K; Hensgens, C; Baldwin, J; Schofield, C (2004)
Deacetoxycephalosporin/deacetylcephalosporin C synthase (DAOC/DACS) is an iron(II) and 2-oxoglutarate-dependent oxygenase involved in the biosynthesis of cephalosporin C in Cephalosporium acremonium. It catalyzes two oxidative reactions, oxidative ring-expansion of penicillin N to deacetoxycephalosporin C, and hydroxylation of the latter to give deacetylcephalosporin C. The enzyme is closely related to deacetoxycephalosporin C synthase (DAOCS) and DACS from Streptomyces clavuligerus, which selectively catalyze ring-expansion or hydroxylation reactions, respectively. In this study, structural models based on DAOCS coupled with site-directed mutagenesis were used to identify residues within DAOC/DACS that are responsible for controlling substrate and reaction selectivity. The M306I mutation abolished hydroxylation of deacetylcephalosporin C, whereas the W82A mutant reduced ring-expansion of penicillin G (an "unnatural" substrate). Truncation of the C terminus of DAOC/DACS to residue 310 (Delta310 mutant) enhanced ring-expansion of penicillin G by approximately 2-fold. A double mutant, Delta310/M306I, selectively catalyzed the ring-expansion reaction and had similar kinetic parameters to the wild-type DAOC/DACS. The Delta310/N305L/M306I triple mutant selectively catalyzed ring-expansion of penicillin G and had improved kinetic parameters (K(m) = 2.00 +/- 0.47 compared with 6.02 +/- 0.97 mm for the wild-type enzyme). This work demonstrates that a single amino acid residue side chain within the DAOC/DACS active site can control whether the enzyme catalyzes ring-expansion, hydroxylation, or both reactions. The catalytic efficiency of mutant enzymes can be improved by combining active site mutations with other modifications including C-terminal truncation and modification of Asn-305.